Adaptive pattern of mangrove species and the mangrove landscaping in the heavy metal polluted area of Eastern Segara Anakan Lagoon, Indonesia - ENDANG HILMI; NORMAN ARIE PRAYOGO; TEUKU JUNAIDI; ARIF MAHDIANA; NABELA FIKRIYYA (Society for Indonesian Biodiversity, 2023)
Abstract. Hilmi E, Prayogo NA, Junaidi T, Mahdiana A, Fikriyya N. 2023. Adaptive pattern of mangrove species and the mangrove landscaping in the heavy metal polluted area of Eastern Segara Anakan Lagoon, Indonesia. Biodiversitas 24: 2927-2937. The mangrove species have specific adaptations to exclude, accumulate, translocate, and exert heavy metal contaminants. Mangrove species' adaptation to Cadmium (Cd) and Zinc (Zn) pollution are shown by their ability to reduce the negative impact of Cd and Zn pollution. This research aimed to analyze the adaptive pattern and mangrove landscaping in Cd and Zn contaminant areas of Eastern Segara Anakan (E-SAL), Indonesia. Cd and Zn content in different tissues (stem, leaves, and root) of 15 mangrove species were analyzed using Atomic Absorption Spectrometric method. Adaptive pattern and mangrove landscaping were assessed using bioaccumulation factor (BAF) and translocation factor (TF). The results showed that the Cd accumulation varied between 0.0610-0.2300 ppm in the stem, 0.0140-0.0480 ppm in leaves, 0.1501-0.3100 ppm in roots, whereas Zn accumulation varied between 5.7781-37.3409 ppm in the stem, 2.3973-32.2859 ppm in leaves, 10.8380-35.842 ppm in roots. Relatively Cd and Zn accumulation was highest in root than other parts. BAF scores of Cd and Zn varied between 0.0111-0.1760 and 0.1936-0.9017, respectively. TF score of Cd and Zn varied between 0.0642-0.9414 and 0.3419-1.3057, respectively. Based on the adaptation pattern, the mangrove landscape showed that Avicennia marina (Forssk.) Vierh., Rhizophora mucronata Lam., and Rhizophora apiculata Blume were the best accumulator of Cd contaminants. At the same time, A. marina, R. apiculata, and X. granatum were the best accumulator of Zn contaminant. The conclusion explains that mangrove species significantly adapt to life and grow in Zn and Cd-polluted areas. Therefore, mangrove landscaping can be developed to reduce the impact of Zn and Cd pollution.